Comercialización de los productos artesanales de madera en Iquitos metropolitano a fin de mejorar la condición socio económica de los artesanos – 2024 - Pinedo Inuma, Danica Mibbet (2025)
This study was carried out in the artisanal centres of Iquitos with the aim of evaluating the marketing of artisanal products made from wood. According to the obtained results, two Associations of Artisanal Producers have been identified in Iquitos, which house 96 marketing posts and are located in the central part of the city. 20 artesanal articles of greater production for marketing have been identified, and 10 forest species for the manufacture of artisanal products have been identified. The prices of the products offered in the market are varied and range from S/.5 to S/.10 soles, the most comfortable ones such as small butterflies, key chains, small glasses, made of topa or pali sangre to products such as large bases made of pali sangre whose cost reaches S/. 2000 or scultures that can reach up to 2500 soles. The greatest consumption of the products corresponds to the national market with 53% of the total volume, the international market with 30% and the local market with 17%. The economic-financial indicators of the artesans are quite low:27% of the total have sab¿vings, 13% own their own home, 7% have other businesses and 14% have no accumulated debts. The artesans activity in Iquitos needs the support of all authorities and businessmen since it is going through a bad moment and has not experienced any development.